Flood risk assessment and management how to specify hydrological loads, their consequences and uncertainties - Schumann, Andreas 1953- (Springer, 2011)
This book examines many aspects of flood risk management in a comprehensive way. As risks depend on hazard and vulnerabilities, not only geophysical tools for flood forecasting and planning are presented, but also socio-economic problems of flood management are discussed. Starting with precipitation and meteorological tools to its forecasting, hydrological models are described in their applications for operational flood forecasts, considering model uncertainties and their interactions with hydraulic and groundwater models. With regard to flood risk planning, regionalization aspects and the options to utilize historic floods are discussed. New hydrological tools for flood risk assessments for dams and reservoirs are presented. Problems and options to quantify socio-economic risks and how to consider them in multi-criteria assessments of flood risk planning are discussed. This book contributes to the contemporary efforts to reduce flood risk at the European scale. Using many real-world examples, it is useful for scientists and practitioners at different levels and with different interests.